Sustainable utilization of foundry waste: Forecasting mechanical properties of foundry sand based concrete using multi-expression programming - Iqbal, Muhammad Farjad; Javed, Muhammad Faisal; Rauf, Momina; Azim, Iftikhar; Ashraf, Muhammad; Yang, Jian; Liu, Qing-feng (The Science of the total environment, 2021)
Waste Foundry sand (WFS), a major solid waste from metal casting industry, is posing a significant environmental threat owing to its disposal to landfills. In this research, an innovative artificial intelligence technique i.e. Multi-Expression Programming (MEP) is applied to model the split tensile strength (ST) and modulus of elasticity (E) of concrete containing waste foundry sand (CWFS). The presented formulations correlate mechanical properties with four input variables i.e. w/c, foundry sand content, superplasticizer content and compressive strength. The results of statistical analysis validate the model accuracy as evident by the low values of objective function (0.033 for E and 0.052 for ST). Moreover, the average error in the predicted values is significantly low i.e. 0.287 MPa and 1.75 GPa for ST and E model, respectively. Parametric study depicts that the models are well trained to accurately predict the trends of mechanical properties with variation in mix parameters. The prediction models can promote the usage of WFS in green concrete thereby preventing waste disposal and contributing towards and sustainable construction. [Display omitted] •WFS, a hazardous solid waste, causes adverse environmental impact.•Artificial intelligence is used to model mechanical properties of green concrete.•Validation and parametric study is performed to ensure the accuracy of models.•Application of proposed models can contribute towards sustainable construction.